IoT Based Pothole Detection and Warning System - Vinita Sharma,Pratik Wavhal, Mrunalinee Thakur (International Journal of Advanced Science and Technology, 2020)
In India, we have a road network of about 9,60,000 kilometres and most of them are poorly con- structed, so potholes are a common artefact. They cause huge damage to vehicles and are one of the major causes of accidents. Nearly 2This paper focuses on detecting and warning drivers about potholes to avoid vehicle damages or accidents. In our system, to identify the potholes, we use ultrasonic sensor, we also use global positioning system receiver (GPS receiver) for identification of geo- graphical location coordinates of the detected potholes. This will give drivers early warnings about the presence of potholes.